A high performance rare earth ion doped organic magnet and preparation method thereof
By doping Eu3+ ions in organic magnets, the problem of magnetic regulation is solved, the magnetization strength and coercivity are significantly improved, and the magnetization is effectively regulated, and the application scenarios are expanded.
Patent Information
- Application Number
- CN202411421378.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-12
AI Technical Summary
Existing organic magnets have defects in magnetic regulation, and cannot achieve fine-tuning of magnetic properties without changing the magnetic type and Curie temperature, and lack magnetic anisotropy.
By doping Eu3+ ions in organic magnets, using their single ion anisotropy and magnetic moment, replacing Cr metal ions, significantly enhancing the magnetization strength and regulating the magnetism, and maintaining the original magnet frame structure and morphology unchanged.
Effective regulation of the magnetism of organic magnets is achieved, the saturation magnetization and coercivity are significantly improved, the gap in magnetic regulation in the existing technology is filled, and the possibility of organic magnets being applied in different scenarios is expanded.
Smart Images

Figure CN118969431B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of organic magnets, and in particular to a high-performance rare earth ion-doped organic magnet and a preparation method thereof. Background Art
[0002] Inorganic magnets are usually composed of pure metals, metal oxides or intermetallic compounds. They are currently widely used in various aspects of national defense, scientific research and daily life, such as radar stealth materials, new energy vehicles and wind power generation, magnetic data storage, medical equipment and engines, etc. However, inorganic magnets also have some disadvantages, such as the need for high-temperature calcination and high magnetic loss during the preparation process. Compared with inorganic magnets, organic magnets have unique advantages, such as diverse molecular types, room-temperature chemical synthesis, low magnetic loss, optoelectronic multifunctional response, etc. Therefore, organic magnets have important application prospects in the ultra-high frequency field, microelectronics industry and lightweight magnetic materials required for aerospace.
[0003] Organic magnets can be divided into two categories: one is pure organic molecules (composed of elements such as C, H, O, and N), whose magnetism comes from the long-range magnetic order formed by the spin of the s or p orbital electrons of organic free radicals through exchange coupling, and the magnetic ordering temperature is usually much lower than room temperature. The other is a charge transfer complex achieved by combining organic ligands with magnetic metal ions, which uses some inherently magnetic ions in transition metals to combine with organic matter to produce magnetic materials with magnetism and other properties. This combination is mostly due to the π-conjugated organic ligands bridging the transition metal ions to form a metal-organic framework or complex, in which the strong hybridization between the d orbital of the metal center and the p orbital of the π-conjugated organic ligand produces unpaired electrons and has magnetism. At the same time, different metal ions can be coupled through superexchange through organic ligands.
[0004] Organic magnets are very close to the performance of permanent magnets that are widely used nowadays. They have good magnetic properties and also have high coercivity. The magnetism of organic magnets can be changed by changing metal ions or organic ligands to form compounds with new structures, but this method has a great change in the magnetism of the original magnets, such as from ferromagnetism to antiferromagnetism or paramagnetism, so this method cannot achieve fine-tuning of the magnetism of organic magnets. In addition, organic magnets usually do not have magnetic anisotropy due to the characteristics of the exchange interaction type and crystal field. Summary of the invention
[0005] The present invention provides a high-performance rare earth ion doped organic magnet and a preparation method thereof, which improves the saturation magnetization intensity and coercive force without changing the macroscopic magnetism and overall framework structure of the original organic magnet itself, thereby realizing magnetic regulation of the organic magnet.
[0006] In order to solve the above technical problems, one of the purposes of the present invention is to provide a method for preparing a high-performance rare earth ion-doped organic magnet, comprising the following steps:
[0007] (1) Add Cr metal precursor and organic ligand into the autoclave reaction equipment, and add Eu 2+ Metal salt, constant temperature reaction;
[0008] (2) Cool to room temperature, wash and dry to obtain Eu 3+ Doped organic magnet products.
[0009] By adopting the above scheme, the present invention dopes Eu into organic magnets. 3+ The ions will not change the main framework structure and morphology of the organic magnet, and the Curie temperature will not change significantly, and the macroscopic magnetism will remain unchanged; the doped Eu 3+ It is in the +3 valence state. Its ionic magnetic moment mainly comes from the 4f shell electrons, showing single ion anisotropy. It usually does not exchange with other ions. When Eu is introduced into the Cr-containing organic magnetic material 3+ When using Eu 3+ Effectively replace the Cr metal ions in organic magnets, the influence on the magnetic properties of the material mainly comes from Eu 3+ Due to its own single-ion anisotropy and magnetic moment contribution, the direction of Eu-doped magnetic domains is the same as that of the original ferromagnet, and the magnetization intensity is significantly greater than that of the original Cr magnetic domains. Therefore, the magnetization can be significantly enhanced and the saturation magnetization intensity can be increased, thereby achieving effective regulation of the magnetic properties of organic magnets.
[0010] This method aims to fill the gap in regulating the magnetic properties of organic magnets and effectively regulate their magnetic properties without changing the type and Curie temperature of organic magnets, which is of great significance for the application of organic magnets in different scenarios.
[0011] As a preferred embodiment, the Cr metal precursor is CrCl2.
[0012] By adopting the above scheme, the Cr metal precursor of the present application is CrCl2, which can ensure the magnetism of the synthesized organic magnet, and the morphology of the synthesized organic magnet is a 2D layered structure. If other Cr-containing metal salts such as CrI2 or CrBr2 are used, it will affect the magnetism after synthesis, and it is very likely to cause the destruction of the layered structure and the disappearance of magnetism.
[0013] As a preferred embodiment, the organic ligand is pyrazine.
[0014] By adopting the above scheme, the magnetic properties of the reaction products of different organic ligands and CrCl2 will be different. For example, the product of the reaction of pyridine and CrCl2 is an antiferromagnetic material with a Neel temperature of 10K, which is completely different from the ferromagnetic material prepared in this application; while the reaction products of different metal ligands such as FeCl2, CoCl2 or NiCl2 and pyrazine are paramagnetic or very low temperature antiferromagnetic, and there is a large difference in magnetic properties. Therefore, the organic magnet synthesized by pyrazine and CrCl2 in this application has excellent ferromagnetic properties, and the morphology has a 2D layered structure. By doping Eu in the organic magnet of this application, 3+ The ions will not change the main framework structure and morphology of the organic magnet of the present application, and the Curie temperature will not change significantly, the macroscopic magnetism will remain unchanged, and at the same time, the magnetization can be significantly enhanced and the saturation magnetization intensity can be improved.
[0015] As a preferred embodiment, the Eu-containing 2+ The metal salt is EuCl2.
[0016] As a preferred embodiment, the Eu-containing 2+ The molar ratio of the metal salt to the Cr metal precursor is (0.05-0.2):(0.8-0.95).
[0017] As a preferred embodiment, the Eu-containing 2+ The molar ratio of the metal salt to the Cr metal precursor is 0.1:0.9.
[0018] By adopting the above scheme, the method for preparing organic magnets of the present application controls the content of Eu 2+ The molar ratio of the metal salt and the Cr metal precursor is 0.1:0.9, which can ensure an appropriate amount of Eu doping to improve the magnetism of the organic magnet. This is because less Eu doping will lead to insufficient improvement in the overall magnetic moment of the organic magnet, while more Eu doping cannot fully participate in the reaction, and more Eu may destroy the ferromagnetic coupling and reduce the magnetism, resulting in a decrease in the saturation magnetization and an increase in the coercive force.
[0019] As a preferred embodiment, the Eu-containing 2+ The molar ratio of the total amount of metal salt and Cr metal precursor to the organic ligand is below 0.11.
[0020] As a preferred embodiment, the Eu-containing 2+ The molar ratio of the total amount of metal salt and Cr metal precursor to the organic ligand is below 0.067.
[0021] As a preferred embodiment, the Eu-containing 2+ The molar ratio of the total amount of metal salt and Cr metal precursor to the organic ligand is between 0.03 and 0.067.
[0022] By adopting the above scheme, the inventors have found through multiple experiments that in the preparation process of the organic magnet of the present application, it is necessary to ensure that the amount of organic ligand added is sufficient. 2+ When the molar ratio of the total amount of metal salt and Cr metal precursor to the organic ligand is below 0.067, a higher synthesis rate can be obtained.
[0023] As a preferred solution, the Eu-doped organic magnet is Eu 3+ Doped CrCl2(pyz)2.
[0024] As a preferred embodiment, in step (1), the isothermal reaction temperature is 200°C and the reaction time is 24 h.
[0025] As a preferred embodiment, in step (1), the isothermal reaction is carried out in an inert gas atmosphere.
[0026] As a preferred embodiment, in step (1), the inert gas is at least one of nitrogen, helium, neon, argon, krypton and xenon.
[0027] As a preferred embodiment, in step (2), at least one of N,N-dimethylformamide, acetonitrile, dimethyl sulfoxide and N-methyl-2-pyrrolidone is sequentially used for washing.
[0028] As a preferred embodiment, in step (2), washing is performed with N,N-dimethylformamide for 1-2 times, and then washing is performed with acetonitrile for 2-3 times.
[0029] As a preferred embodiment, the autoclave reaction equipment is a stainless steel autoclave reactor lined with polytetrafluoroethylene.
[0030] In order to solve the above technical problems, the second object of the present invention is to provide a high-performance rare earth ion-doped organic magnet.
[0031] In order to solve the above technical problems, the third object of the present invention is to provide an application of a high-performance rare earth ion-doped organic magnet in the field of preparing magnetic materials.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] This application aims to fill the gap in regulating the magnetic properties of organic magnets, effectively regulate their magnetic properties without changing the type and Curie temperature of organic magnets, and dope Eu in organic magnets. 3+ The ions will not change the main framework structure and morphology of the organic magnet, and the Curie temperature will not change significantly, and the macroscopic magnetism will remain unchanged; using Eu 3+ Effectively replace the Cr metal ions in organic magnets, the influence on the magnetic properties of the material mainly comes from Eu 3+Due to its own single-ion anisotropy and magnetic moment contribution, the direction of the Eu-doped magnetic domain is the same as the original ferromagnet, and the magnetization intensity is significantly greater than that of the original Cr magnetic domain. Therefore, the magnetization can be significantly enhanced, which is of great significance for the expanded application scenarios of organic magnets. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 : is a schematic flow chart of a method for preparing a high-performance rare earth ion-doped organic magnet in Example 1 of the present invention;
[0035] Figure 2 : XRD images of organic magnets prepared in Example 1 and Comparative Examples 1-2 of the present invention (Note: 0.1Sm doping - Comparative Example 2; 0.1Eu doping - Example 1; undoped - Comparative Example 1);
[0036] Figure 3 : SEM images of organic magnets prepared in Example 1 and Comparative Examples 1-2 of the present invention (Note: a-Comparative Example 1; b-Example 1; c-Comparative Example 2);
[0037] Figure 4 : Schematic diagram of the structure of the vibrating sample magnetometer;
[0038] Figure 5 : ZFC and FC of 500 Oe of organic magnets were prepared for Example 1 and Comparative Examples 1-2 of the present invention (Note: undoped - Comparative Example 1; 0.1 Eu doped - Example 1; 0.1 Sm doped - Comparative Example 2);
[0039] Figure 6 : The first quadrant diagram of the hysteresis loop of the organic magnets prepared in Example 1 and Comparative Examples 1-2 of the present invention at 2K (Note: undoped - Comparative Example 1; 0.1 Eu doped - Example 1; 0.1 Sm doped - Comparative Example 2);
[0040] Figure 7 : The first principle calculation results of the organic magnets prepared in Example 1 and Comparative Examples 1-2 of the present invention (Note: blue balls are Cr ions; pink balls are Eu ions; red balls are Sm ions; the marked values are the magnetic moments of individual atoms in the system, in μ B ; a-top view of the structure of comparative example 1 calculated by first principles; b-top view of the structure of embodiment 1 calculated by first principles; c-top view of the structure of comparative example 2 calculated by first principles; d-magnetic moment ordering of metal atoms in comparative example 1; e-magnetic moment ordering of metal atoms in embodiment 1; f-magnetic moment ordering of metal atoms in comparative example 2). DETAILED DESCRIPTION
[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] This application uses Eu 3+ Effectively replace transition metal ions in organic magnets, Eu 3+ It is in the +3 valence state. Its ionic magnetic moment mainly comes from the 4f shell electrons, showing single ion anisotropy. It usually does not exchange with other ions. When Eu is introduced into the material 3+ When the influence on the magnetic properties of the material is mainly from Eu 3+ The single ion anisotropy and magnetic moment contribution of the organic magnet can effectively control the magnetism of the organic magnet. This method aims to fill the gap in the regulation of the magnetism of organic magnets and effectively regulate their magnetism without changing the type and Curie temperature of the organic magnet, which is of great significance for the application of organic magnets in different scenarios.
[0043] Example 1
[0044] A method for preparing a high-performance rare earth ion-doped organic magnet, specifically Eu 3+ Doping CrCl2(pyz)2 comprises the following steps:
[0045] (1) Eu 3+ The preparation process of doped CrCl2(pyz)2 was carried out in a dry N2 atmosphere. CrCl2, EuCl2 and pyrazine were added to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave reactor. The amount of CrCl2 added was 1.44 mol, the amount of pyrazine added was 25 mol, and the molar ratio of EuCl2 to CrCl2 was 0.1:0.9. The reaction temperature was 200 °C in an oven for 24 h.
[0046] (2) The reactor was cooled to room temperature, washed once with 20 mL of N,N-dimethylformamide and twice with 20 mL of acetonitrile to obtain Eu 3+ The purple-black microcrystalline product doped with CrCl2(pyz)2 was vacuum dried to obtain the final sample. The product yield was calculated to be 75.5% after detection. The yield was calculated based on the molar ratio of the total consumption of EuCl2 and CrCl2.
[0047] Example 2
[0048] A method for preparing a high-performance rare earth ion-doped organic magnet, specifically Eu 3+Doping CrCl2(pyz)2 comprises the following steps:
[0049] (1) Eu 3+ The preparation process of doped CrCl2(pyz)2 was carried out in a dry N2 atmosphere. CrCl2, EuCl2 and pyrazine were added to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave reactor. The amount of CrCl2 added was 1.52 mol, the amount of pyrazine added was 25 mol, and the molar ratio of EuCl2 to CrCl2 was 0.05:0.95. The reaction temperature was 200 °C in an oven for 24 h.
[0050] (2) The reactor was cooled to room temperature, washed once with 20 mL of N,N-dimethylformamide and twice with 20 mL of acetonitrile to obtain Eu 3+ The purple-black microcrystalline product doped with CrCl2(pyz)2 was vacuum dried to obtain the final sample. The product yield was calculated to be 72.8% after detection. The yield was calculated based on the molar ratio of the total consumption of EuCl2 and CrCl2.
[0051] Example 3
[0052] A method for preparing a high-performance rare earth ion-doped organic magnet, specifically Eu 3+ Doping CrCl2(pyz)2 comprises the following steps:
[0053] (1) Eu 3+ The preparation process of doped CrCl2(pyz)2 was carried out in a dry N2 atmosphere. CrCl2, EuCl2 and pyrazine were added to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave reactor. The amount of CrCl2 added was 1.28 mol, the amount of pyrazine added was 25 mol, and the molar ratio of EuCl2 to CrCl2 was 0.2:0.8. The reaction temperature was 200 °C in an oven for 24 h.
[0054] (2) The reactor was cooled to room temperature, washed once with 20 mL of N,N-dimethylformamide and twice with 20 mL of acetonitrile to obtain Eu 3+ The purple-black microcrystalline product doped with CrCl2(pyz)2 was vacuum dried to obtain the final sample. The product yield was calculated to be 76.6% after detection. The yield was calculated based on the molar ratio of the total consumption of EuCl2 and CrCl2.
[0055] Example 4
[0056] A method for preparing a high-performance rare earth ion-doped organic magnet, specifically Eu 3+ Doping CrCl2(pyz)2 comprises the following steps:
[0057] (1) Eu 3+ The preparation process of doped CrCl2(pyz)2 was carried out in a dry N2 atmosphere. CrCl2, EuCl2 and pyrazine were added to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave reactor. The amount of CrCl2 added was 1.44 mol, the amount of pyrazine added was 15 mol, and the molar ratio of EuCl2 to CrCl2 was 0.1:0.9. The reaction temperature was 200 °C in an oven for 24 h.
[0058] (2) The reactor was cooled to room temperature, washed once with 20 mL of N,N-dimethylformamide and twice with 20 mL of acetonitrile to obtain Eu 3+ The purple-black microcrystalline product doped with CrCl2(pyz)2 was vacuum dried to obtain the final sample. The product yield was calculated to be 55.1% after testing. The yield was calculated based on the molar ratio of the total amount of EuCl2 and CrCl2 consumed. It can be found that the less pyrazine added during the preparation process of this embodiment resulted in a lower synthesis rate of the final product compared to Example 1, and the synthesis efficiency was low.
[0059] Example 5
[0060] A method for preparing a high-performance rare earth ion-doped organic magnet, specifically Eu 3+ Doping CrCl2(pyz)2 comprises the following steps:
[0061] (1) Eu 3+ The preparation process of doped CrCl2(pyz)2 was carried out in a dry N2 atmosphere. CrCl2, EuCl2 and pyrazine were added to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave reactor. The amount of CrCl2 added was 1.44 mol, the amount of pyrazine added was 30 mol, and the molar ratio of EuCl2 to CrCl2 was 0.1:0.9. The reaction temperature was 200 °C in an oven for 24 h.
[0062] (2) The reactor was cooled to room temperature, washed once with 20 mL of N,N-dimethylformamide and twice with 20 mL of acetonitrile to obtain Eu 3+ The purple-black microcrystalline product doped with CrCl2(pyz)2 was vacuum dried to obtain the final sample. The product yield was calculated to be 75.7% after testing. The yield was calculated based on the molar ratio of the total amount of EuCl2 and CrCl2 consumed. It can be found that the synthesis rate of the final product increased with the increase in the pyrazine content added during the preparation process of this embodiment, and was not much different from that of Example 1, indicating that adding sufficient pyrazine during the preparation process of this application can increase the synthesis rate of the final product to a limited extent.
[0063] Comparative Example 1
[0064] A method for preparing an organic magnet, specifically CrCl2(pyz)2, comprises the following steps:
[0065] (1) The preparation process of CrCl2(pyz)2 was carried out in a dry N2 atmosphere. CrCl2 and pyrazine were added to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave reactor. The amount of CrCl2 added was 1.6 mol and the amount of pyrazine added was 25 mol. The reaction temperature was 200 °C in an oven for 24 h.
[0066] (2) The reactor was cooled to room temperature, washed once with 20 mL of N,N-dimethylformamide and twice with 20 mL of acetonitrile to obtain a purple-black microcrystalline product of CrCl2(pyz)2. The final sample was dried in vacuo and the product yield was 70.5% after testing. The yield was calculated based on the molar ratio of the total amount of CrCl2 consumed. It can be found that the synthesis rate of the final product of this comparative example without Eu doping is lower than that of Examples 1-3, indicating that doping Eu in the organic magnet helps to improve the synthesis rate of the final product.
[0067] Comparative Example 2
[0068] A method for preparing an Sm-doped organic magnet, specifically Sm 3+ Doping CrCl2(pyz)2 comprises the following steps:
[0069] (1) Sm 3+ The preparation process of doped CrCl2(pyz)2 was carried out in a dry N2 atmosphere. CrCl2, SmCl2 and pyrazine were added to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave reactor. The amount of CrCl2 added was 1.44 mol, the amount of pyrazine added was 25 mol, and the molar ratio of SmCl2 to CrCl2 was 0.1:0.9. The reaction was placed in an oven at a temperature of 200 °C and a reaction time of 24 h.
[0070] (2) The reactor was cooled to room temperature, washed once with 20 mL of N,N-dimethylformamide and twice with 20 mL of acetonitrile to obtain Sm 3+ The purple-black microcrystalline product doped with CrCl2(pyz)2 was vacuum dried to obtain the final sample. The product yield was calculated to be 75.3% after detection. The yield was calculated based on the molar ratio of the total consumption of SmCl2 and CrCl2.
[0071] Performance testing
[0072] 1. Morphology and structure test: Scanning electron microscopy (SEM) and X-ray diffraction (XRD) tests were performed on the samples of Example 1 and Comparative Examples 1-2.
[0073] like Figure 2 As shown, the undoped CrCl2(pyz)2 sample, 0.1Eu 3+ Doped CrCl2(pyz)2 samples and 0.1 Sm 3+ The XRD peak positions of the three main peaks between 10° and 20° of the CrCl2(pyz)2-doped samples are the same, and the positions of other peaks are also basically the same. 3+ XED detection of the CrCl2(pyz)2 doped sample confirmed that the diffraction characteristics formed were basically consistent with those in Example 1.
[0074] like Figure 3 As shown, the undoped CrCl2(pyz)2 sample, 0.1Eu 3+ Doped CrCl2(pyz)2 samples and 0.1 Sm 3+ The SEM morphologies of the doped CrCl2(pyz)2 samples at a scale of 500nm are basically the same, and all are 2D layered structures. It can be concluded that the doped ions in Example 1 and Comparative Example 2 did not change the main framework structure and morphology of the organic magnet CrCl2(pyz)2.
[0075] 2. Magnetic test: The magnetic test of samples is carried out by the vibrating sample magnetometer test of the comprehensive physical property measurement system PPMS option. The results of the vibrating sample magnetometer are as follows: Figure 4 shown.
[0076] 1) The samples of Example 1 and Comparative Examples 1-2 were characterized by ZFC (zero field cooling) and FC (field cooling). The results are as follows: Figure 5 As shown, by comparing the three samples, it was found that the ZFC and FC of the three had almost no change in shape and their ZFC and FC overlapped when the temperature reached around 55 K, which means that the Curie temperatures of the three were all around 55 K.
[0077] 2) Determine the magnetization intensity of the samples of Example 1 and Comparative Examples 1-2. The test method is the hysteresis loop test of ferromagnetic materials. The test results are as follows: Figure 6 shown.
[0078] Figure 6 For undoped CrCl2(pyz)2 samples, 0.1Eu 3+ Doped CrCl2(pyz)2 samples and 0.1 Sm 3+ The first quadrant of the hysteresis loop of the doped CrCl2(pyz)2 sample at 2K. From the figure, we can see that the three samples have hysteresis below the Curie temperature of 55 K, that is, the horizontal axis (magnetic field) of the loop in the figure is still not zero when the vertical axis (magnetic moment) is 0, which is consistent with Figure 5The Curie temperature of 55 K shown can indicate that doping does not change the macroscopic magnetism of the sample. The samples of Example 1 and Comparative Examples 1-2 are all ferromagnetic / ferrimagnetic samples with a Curie temperature of 55 K.
[0079] At the same time, from Figure 6 It can be seen that the saturation magnetization of the undoped CrCl2(pyz)2 sample, the 0.1Eu-doped CrCl2(pyz)2 sample and the 0.1Sm-doped CrCl2(pyz)2 sample at 2 K is 1.64μ B , 1.83μ B and 1.51μ B The low-temperature saturation magnetization of doped and undoped ion samples has a significant change, among which 0.1Eu-doped CrCl2(pyz)2 sample increases the saturation magnetization of the original sample, while 0.1Sm-doped CrCl2(pyz)2 sample reduces the saturation magnetization of the original sample.
[0080] The calculation formula of saturation magnetization is:
[0081] (1)
[0082] In the formula, Ms is the saturation magnetization (unit: μ B ), M is the mass (in g), M' is the magnetic moment (in emu) obtained at 2 K, and M" is the molar mass of the sample.
[0083] 3) To further confirm and explain the organic magnet samples doped with Eu 3+ After the changes, the first principle calculations were performed on the three samples of Examples 1-3 and Comparative Examples 1-2. The results are shown in Tables 1 and Figure 7 As shown, the differences in saturation magnetization, coercive force and fine structure between doped and undoped organic magnets are shown.
[0084] Table 1 - Calculated and experimental magnetic results of samples of Examples 1-3 and Comparative Examples 1-2 at 2K
[0085]
[0086] like Figure 7 As shown in the figure, Eu doping and Sm doping replace one of the Cr in the original organic magnet CrCl2(pyz)2 with Sm / Eu elements, thus affecting the magnetism. The direction of the Eu-doped magnetic domain is the same as that of the original ferromagnet, and the magnetization intensity is significantly greater than that of the original Cr domain, so the magnetization can be significantly enhanced. The calculated saturation magnetization intensity of Eu-doped CrCl2(pyz)2 is 2.29μ B , the experimental value is 1.83μ BThere is an error between the experimental value and the calculated value, which is related to the experimental environment. The direction of the Sm-doped magnetic domain is opposite to that of the original ferromagnet, the magnetization intensity is low, and it will induce the reversal of some Cr atomic domains, thus significantly weakening the magnetization. The calculated saturation magnetization intensity of Sm-doped CrCl2(pyz)2 is 1.64μ B , the experimental value is 1.51μ B .
[0087] As shown in Table 1, the saturation magnetization of Examples 2-3 is lower than that of Example 1. This is because Example 2 has less Eu doping, which leads to insufficient improvement in the overall magnetic moment of the organic magnet, and Example 3 has more Eu doping, which cannot fully participate in the reaction and may destroy the ferromagnetic coupling and reduce the magnetism, resulting in a decrease in saturation magnetization and an increase in coercive force.
[0088] The calculated and experimental data of saturation magnetization have the same overall trend, which further verifies that Eu doping will significantly change the saturation magnetization of the original organic magnet. Therefore, by doping Eu ions in the precursor, the magnetization, coercive force and anisotropy of the organic magnet can be effectively regulated and improved.
[0089] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. It is particularly pointed out that for those skilled in the art, any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a high-performance rare earth ion-doped organic magnet, characterized in that: The following steps are involved: (1) Add Cr metal precursor and organic ligand into the autoclave reaction equipment, and add Eu 2+ Metal salt, constant temperature reaction; (2) Cool to room temperature, wash and dry to obtain Eu 3+ Doped organic magnetic products; The Eu 2+ The molar ratio of the metal salt and the Cr metal precursor is (0.05-0.2): (0.8-0.95), and the Eu 2+ The molar ratio of the total amount of metal salt and Cr metal precursor to the organic ligand is below 0.
11.
2. The method for preparing a high-performance rare earth ion-doped organic magnet according to claim 1, characterized in that: The Cr metal precursor is CrCl2.
3. The method for preparing a high-performance rare earth ion-doped organic magnet according to claim 1, characterized in that: The organic ligand is pyrazine.
4. The method for preparing a high-performance rare earth ion-doped organic magnet according to claim 1, characterized in that: The Eu 2+ The metal salt is EuCl2.
5. The method for preparing a high-performance rare earth ion-doped organic magnet according to claim 1, characterized in that: In step (1), the isothermal reaction temperature is 200°C and the reaction time is 24 h.
6. The method for preparing a high-performance rare earth ion-doped organic magnet according to claim 1, characterized in that: In step (2), washing is performed using at least one of N,N-dimethylformamide, acetonitrile, dimethyl sulfoxide and N-methyl-2-pyrrolidone in sequence.
7. The method for preparing a high-performance rare earth ion-doped organic magnet according to claim 1, characterized in that: The autoclave reaction equipment is a stainless steel autoclave reactor lined with polytetrafluoroethylene.
8. A high-performance rare earth ion-doped organic magnet prepared by the method for preparing a high-performance rare earth ion-doped organic magnet as claimed in any one of claims 1 to 7.
9. Use of the high-performance rare earth ion-doped organic magnet according to claim 8 in the field of preparing magnetic materials.
